Adrenal bleeding in neonates: report of 37 cases - Demirel, Nihal; Baş, Ahmet Yağmur; Zenciroğlu, Ayşegül; Taşci-Yildiz, Yasemin (The Turkish Journal of Pediatrics, 2011)
Adrenal hemorrhage is more common in neonates than in children or adults. The incidence of detected cases ranges from 1.7 to 2.1 per 1000 births. Because adrenal bleeding may remain asymptomatic, the real occurrence is probably higher. In this retrospective study, we evaluated epidemiologic properties, risk factors and clinical presentations of adrenal hemorrhage in 37 term newborn babies diagnosed as adrenal hemorrhage with abdominal ultrasonography between January 2003 and July 2007 in Dr. Sami Ulus Children's Hospital Neonatal Intensive Care Unit (NICU). We also evaluated the role of adrenal hemorrhage among the etiologic factors of unexplained jaundice. Abdominal ultrasonography was applied to 2280 newborns, and 37 newborns (25 male, 12 female) were diagnosed as adrenal hemorrhage (1.6%). The male/female ratio was 2.08. The average age and birth weight at admission were 4.9 +/- 0.3 days and 3333 +/- 939 g, respectively. Adrenal hemorrhage was right-sided in 24, left-sided in 9 and bilateral in 4 newborns. Resolution time of adrenal hemorrhage was a minimum of 3 months, maximum of 9 months in ultrasonographic follow-up. The most common clinical feature in infants with adrenal hemorrhage was jaundice, which was observed in 67.6% of cases (n = 25). We advise that, in cases of hyperbilirubinemia of unknown etiology, adrenal hemorrhage must be kept in mind. We recommend abdominal ultrasonography for further evaluation.